Desenvolvimento e caracterização de composições elastoméricos de EPDM com redução no teor de óxido de zinco - Gujel, Angela Artini (My University, 2016)
Zinc oxide nanoparticle (nano ZnO) is a kind of inorganic multifunctional filler, which has extensive uses in rubber additives. Notably, most of relevant researches about nano ZnO focused on using them as a substitute of conventional ZnO and an essential cure activator for rubber crosslinking by sulfur or sulfur donors in rubber composites. In this work, the effect of three kinds of ZnO on the properties of ethylene, propylene and diene (EPDM) elastomeric compounds was investigated. Standard ZnO (sZnO), nano ZnO (ZnO 40) and nano ZnO dispersed in CaCO3 (ZnO 30) were used and their characteristics were analyzed. The characterizations of these ZnO were carried out by atomic absorption spectrometry, X-ray diffraction, surface area, scanning electron microscopy, pore and particle size distribution. The elastomeric composites were processed in an industrial two-roll mill and the different ZnO were added in a laboratory two-roll mill. A usual composition to bus body rubber profile were prepared with varying the proportion of ZnO (1, 2, 3, 4 and 5 parts per hundred of rubber (phr)). To ZnO 40 and ZnO 30 ten composites were developed (1, 2, 3, 4 and 5 phr), including a compound without ZnO (White sample). The cure properties were determined in an oscillating disk rheometer. The unvulcanized compositions are also characterized by a Mooney viscometer and a rubber process analyzer (RPA). After vulcanization, the compositions had their physical- mechanical properties analyzed, as well as scanning electron microscopy. The thermal oxidative aging, the parameters and degradation kinetic mechanisms were studied for the compounds with the same mass content of Zn (sZnO 4 phr, ZnO 30 3 phr and ZnO 40 2 phr), as well as the white sample. The results of these investigations showed that ZnO 30 and ZnO 40 have a smaller particle size and higher surface area, making them more reactive and classifying them as nano ZnO. The results of the investigation of the effect of different types of zinc oxide in the EPDM composites were satisfactory, since the same results were obtained with lower amounts of ZnO, particularly with the use of nano ZnO. The non-isothermal degradation process of EPDM rubber compounds were investigated with thermogravimetric analysis (TGA) and derivative thermogravimetry (DTG), using the different calculation procedures. It was found that the values of activation energy of the composition with ZnO 30 and ZnO 40 showed higher results to sZnO, confirming the higher thermal stability. The degradation reaction mechanism determined by the method Coats Redfern (CR) and confirmed by Criado method was the F1 type, can be described by the random scission mechanism, in terms of the first order kinetics. Thus, the use of nano ZnO in elastomeric compositions became interesting, economically viable, important for the environment and it could be a reduction of Zn in the compositions without prejudice to the mechanical performance of the artifacts.
Óxidos de zinco (ZnO), com partículas de tamanho nano (nano ZnO) são um tipo de carga inorgânica multifuncional, que apresenta um vasto uso e importância em formulações elastoméricas. Notavelmente, as mais relevantes pesquisas com nano ZnO estão direcionadas em usá-lo como um substituto do ZnO convencional e, que tem a função principal de ativador de vulcanização para sistemas com enxofre ou doadores de enxofre para composições de borracha. Neste trabalho, o efeito de três tipos de ZnO foi investigado em compostos com terpolímero de etileno-propileno-dieno (EPDM). ZnO convencional (sZnO), nano ZnO (ZnO 40) e nano ZnO disperso em carbonato de cálcio (ZnO 30) e suas características analisadas. A caracterização destes óxidos de zinco foram através de análises de absorção atômica, difração de raios X, microscopia eletrônica de varredura, área superficial específica e distribuição de tamanho de partículas e poros. As composições elastoméricas foram processadas em um misturador de rolos industrial e os diferentes tipos de ZnO foram adicionados em um misturador de rolos de laboratório. Uma composição para perfis automotivos foi preparada variando a quantidade de sZnO (1, 2, 3, 4 e 5 partes por cem de borracha (phr)). Para ZnO 30 e ZnO 40, dez composições foram desenvolvidas (1, 2, 3, 4, e 5 phr), além de um composto sem a adição de ZnO (amostra Branco). As propriedades de cura foram determinadas a partir de um reômetro de disco oscilatório. As composições não vulcanizadas também foram caracterizadas por um viscosímetro Mooney e um analisador de processamento de borracha (RPA). Após a vulcanização, as amostras tiveram suas propriedades físico-mecânicas analisadas, bem como por microscopia eletrônica de varredura. O envelhecimento acelerado em estufa, os parâmetros e mecanismos cinéticos de degradação foram estudados para os compostos com mesmo teor em massa de Zn (sZnO 4 phr, ZnO 30 3 phr e ZnO 40 2 phr), além da amostra Branco. Os resultados destas investigações demonstraram que ZnO 30 e ZnO 40 apresentam menor tamanho de partícula e maior área superficial, tornando-os mais reativos e classificando-os como nano ZnO. O efeito dos três diferentes ZnO nas propriedades físico-mecânicas das composições foram satisfatórios, demonstrando que resultados similares são obtidos utilizando menores teores de ZnO na formulação, principalmente com o uso de nano ZnO. A partir dos cálculos de energia de ativação, constatou-se que com o uso de ZnO 30 e ZnO 40 os valores desta propriedade foram superiores ao sZnO, confirmando a maior estabilidade térmica. O mecanismo de reação de degradação determinado pelo método de Coats Redfern (CR) e confirmado pelo método de Criado foi do tipo F1, que significa uma reação com cisão randômica da cadeia polimérica, em termos de cinética de primeira ordem. Assim, o uso de nano ZnO torna-se interessante, economicamente viável e importante para o meio ambiente, pois conseguiu-se uma redução de Zn nas composições sem prejuízo ao desempenho mecânico dos artefatos.
Keywords: Zinco; Elastômeros; Meio ambiente; Ciência dos materiais; Zinc; Elastomers; Environment